To find the value of \( x \) after determining \( y = -2 \), we can substitute \( y \) back into one of the original equations. Let’s use the first equation from the system:
\[ 4x - 7y = 28 \]
Substituting \( y = -2 \):
\[ 4x - 7(-2) = 28 \] \[ 4x + 14 = 28 \] \[ 4x = 28 - 14 \] \[ 4x = 14 \] \[ x = \frac{14}{4} = \frac{7}{2} = 3.5 \]
Thus, the solution to the system of equations is:
\[ \left( \frac{7}{2}, -2 \right) \quad \text{or} \quad (3.5, -2) \]
So the final answer is:
\[ \left( 3.5, -2 \right) \]